2015
DOI: 10.1180/minmag.2015.079.6.29
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cycling: impact on bentonite permeability

Abstract: Due to its favourable properties, in particular, low permeability and swelling capacity, bentonite has been favoured as an engineered-barrier and backfill material for the geological storage of radioactive waste. To ensure its safe long-term performance it is important to understand any changes in these properties when the material is subject to heat-emitting waste. As such, this study investigates the hydraulic response of bentonite under multi-step thermal loading subject to a constant-volume boundary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This has been attributed to the reduction in water viscosity with increasing temperature [25]. However, Zihms and Harrington [26] found that the sensitivity of bentonite permeability to temperature could not entirely be explained by changes in water viscosity. Repository designs will need to address possible variations in the surrounding temperature of the disposal site and ensure that the maximum design temperature is not exceeded [27,28].…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…This has been attributed to the reduction in water viscosity with increasing temperature [25]. However, Zihms and Harrington [26] found that the sensitivity of bentonite permeability to temperature could not entirely be explained by changes in water viscosity. Repository designs will need to address possible variations in the surrounding temperature of the disposal site and ensure that the maximum design temperature is not exceeded [27,28].…”
Section: Introductionmentioning
confidence: 96%
“…The disadvantage of the isotropic system was that the surface of the clay could not be instrumented. In this paper, we combine new measurements on the sensitivity of permeability to temperature with a reanalysis of previous data (constant volume radial flow (CVRF) experiment CVRF-1) originally presented by Zihms and Harrington [26]. The results of four experiments presented here provide details of the intrinsic permeability, the total stress, the swelling pressure and the porewater pressure during thermal loading of compact bentonite.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations